Cognitive and Linguistic Influences on EFL Real Word and Pseudoword Spelling: Predictors and Error Analysis - Heike Mlakar; Joanna Hirst-Plein; Martin J. Koch (Languages)
The present study aimed to enhance the understanding of the spelling processes used by young German-speaking learners of English as a foreign language (EFL). Specifically, we sought to (1) compare the children’s accuracy in spelling English real words versus pseudowords to elucidate the role of lexical and sublexical knowledge, and (2) determine which cognitive (phonological awareness, phonological short-term memory, working memory, nonverbal intelligence) and linguistic skills (English receptive grammar and vocabulary) underlie learners’ spelling abilities and misspellings (phonological and orthographic). We followed participants (N = 101) for two years, from the beginning of grade 3 to the end of grade 4. Cognitive skills and linguistic abilities were determined using standardized assessment procedures. Our results indicate that the learners in our study demonstrated greater accuracy in spelling English real words compared to pseudowords. English grammar knowledge significantly predicted real word and pseudoword spelling accuracy, as well as the number of phonological errors, which was the predominant error category. English vocabulary knowledge was a predictor for real word spelling, while nonverbal intelligence predicted pseudoword spelling accuracy. Phonological short-term memory positively predicted the number of orthographic errors (phonologically plausible misspellings but lacking orthographic conventions).